FORMATION OF PROFESSIONAL COMPETENCE OF BACHELORS OF FOOD TECHNOLOGIES IN THE PROCESS OF STUDYING PROFESSIONAL DISCIPLINES - Прилипко, Татьяна (SWorldJournal, 2025)
The article is devoted to the substantiation of a strategy for the study of future food technologists of professional disciplines aimed at forming competences that will help improve personal and public health and well -being, ensure the requirements of su